2008
DOI: 10.1002/app.29052
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardancy behaviors and structural properties of polypropylene/nano‐SiO2composite textile filaments

Abstract: The number of efforts about modifying the properties of polymeric fibers by organic or inorganic particles has increased recently because of high-tech applications of textiles. In addition to these attempts, the discovery of nanotechnology also leads to the development of nanoparticles for various end uses such as nanocomposite fibers. In this article, we aimed to produce slow burning or flame retardant polypropylene filaments for carpet pile yarns by incorporating SiO 2 nanoparticles into polymer. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Silica nano particles are also the thermal barrier of oxygen that improves its flame dilatory property. ERDEM et al, (2009) also reported the improvement of the flame dilatory property with the addition of nanosilica.…”
Section: Flammability Treatmentmentioning
confidence: 95%
“…Silica nano particles are also the thermal barrier of oxygen that improves its flame dilatory property. ERDEM et al, (2009) also reported the improvement of the flame dilatory property with the addition of nanosilica.…”
Section: Flammability Treatmentmentioning
confidence: 95%
“…Silica nanoparticles also formed a thermal barrier against oxygen and improved the property of flame deterrence. Erdem et al (2009) also reported the improvement of flame postponement under the effect of the addition of nanosilica. In addition, an enhancement of nanosilica particles could occupy part of the voids and reduce pores; therefore, the accessibility of oxygen for ignition would be more difficult.…”
Section: Limited Oxygen Indexmentioning
confidence: 92%
“…Flame-retardant materials are used in a wide range of applications e.g. textile, aerospace and automotive application (Erdem et al, 2009;Mostashari, 2008). Nowadays, many studies on the fire retardancy of PET have been done, in particular, different additives such as: phosphorus species (Chapple & Ferg, 2006;Zhu et al, 2004;Rohringer et al, 1975;Goodman & Sheanan, 1990;Ge, 2008;Asrar, 1999), silica particles (Sequeira et al, 2007) and halogen compounds (Wilson et al, 1969) have been investigated to reach this goal.…”
Section: Introductionmentioning
confidence: 99%